The requirement for closed reduction of dorsally displaced unstable distal radius fractures before operative treatment: a randomized controlled study - Löw, Steffen; Papay, Marion; Spies, Christian; Unglaub, Frank; Eingartner, Christoph (Deutsches Ärzteblatt, 2020)
BACKGROUND: Dorsally displaced distal radius fractures are generally treated with closed reduction followed by casting. Current evidence suggests that fracture reduction is of no benefit before either conservative or surgical treatment. It has not been studied to date whether the degree of pain suffered by the patient during preoperative casting is any different if the fracture is reduced beforehand. - METHODS: In a prospective, randomized trial, dorsally displaced unstable distal radius fractures were treated surgically, either with or without prior closed reduction (22 and 25 patients, respectively). The primary endpoint was the difference between the pain score (on the Visual Analog Scale) on day 1 after treatment and the initial pain score on presentation. The secondary endpoints included the clinical and radiological outcome and any damage to the median nerve. Moreover, the Krimmer score (strength, mobility, pain, and function of the wrist joint) an the DASH score (Disability of the Arm, Shoulder and Hand) were determined 3 and 12 months after treatment. This trial has been registered with the number DRKS00010570. - RESULTS: With regard to the primary endpoint on day 1 after treatment, there was a statistically significant non-inferiority of the group without reduction, compared to the group with reduction. Sensory disturbances appeared at similar frequencies in the two groups four to six weeks after treatment (9.5% with reduction, 9.1% without). At 12 months, the Krimmer and DASH scores of patients whose fractures had not been reduced were no worse than those of patients whose fractures had been reduced (96 and 7 versus 96.5 and 4.5, respectively; p-values for non-inferiority, 0.004 and 0.008). - CONCLUSION: This trial shows that dispensing with closed reduction before casting as a preliminary to planned surgery yields no disadvantage. Thus, in the authors' view, routine reduction is not warranted.